Copernican Revolution of I. Kant - Karosas, Justinas (Problemos, 1990)
I. Kant is the first thinker, who began the radical change in the traditional orientation of philosophy. In his philosophy a shift from substantiality to free acting subject takes place. That is why in the philosophy alongside with the theoretical parameter of reality a new parameter, namely, the evaluative one, or that of autonomous practical reason, appears. In I. Kant's opinion, the new parameter makes it possible to look into the specific region of the being, namely, into the essence of human being as thing in itself. I. Kant's philosophy, is said, has marked the beginnings of the collapse of omnipotence of cognitive theoretical reason.